Protection of Oligodendrocytes Through Neuronal Overexpression of the Small GTPase Ras in Hyperoxia-Induced Neonatal Brain Injury - Serdar, Meray; Herz, Josephine; Kempe, Karina; Winterhager, Elke; Jastrow, Holger; Heumann, Rolf; Felderhoff-Müser, Ursula; Bendix, Ivo (Frontiers in Neurology, 2018)
Prematurely born infants are highly susceptible to a variety of environmental factors, such as inflammation, drug exposure and also high environmental oxygen concentrations. Hyperoxia induces perinatal brain injury affecting white and gray matter development. It is well known that mitogen activated protein kinase signaling is involved in cell survival, proliferation and differentiation. Therefore, we aim to elucidate cell-specific responses of neuronal overexpression of the small GTPase Ras on hyperoxia-mediated brain injury. Six day old (P6) synRas mice (neuronal Ras overexpression under the synapsin promoter) or wildtype littermates were kept under hyperoxia (80% oxygen) or room air (21% oxygen) for 24 h. Apoptosis was analyzed by Western blot of cleaved Caspase-3 and neuronal and oligodendrocyte degeneration via immunohistochemistry. Short-term differentiation capacity of oligodendrocytes was assessed by quantification of myelin basic protein (MBP) expression at P11. Long-lasting changes of hyperoxia-induced alteration of myelin structures were evaluated via transmission electron microscopy in young adult animals (P42). Western blot analysis of active Caspase-3 demonstrates a significant upregulation in wildtype littermates exposed to hyperoxia whereas synRas mice did not show any marked alteration of cleaved Caspase-3 protein levels. Immunohistochemistry revealed a protective effect of neuronal Ras overexpression on neuron and oligodendrocyte survival. Hyperoxia-induced hypomyelination in wildtype littermates was restored in synRas mice. These short-term protective effects through promotion of neuronal survival translated into long-lasting improvement of ultrastructural alterations of myelin sheaths in mice with neuronal overexpression of Ras compared to hyperoxic wildtype mice. Our data suggest that transgenic increase of neuronal Ras activity in the immature brain results in secondary protection of oligodendrocytes from hyperoxia-induced white matter brain injury.